The use of adsorbents in the reduction of petrol volatile organic compound (VOC) emissions - Goh, Bee Min (2004)
There has been growing concern over the impact of volatile organic compounds (VOCs) emissions since the implementation of self service petrol filling in Malaysia. High exposure to VOCs at petrol stations has been known to cause some hazardous effects on atmospheric environment and human health. The basis of this study was to determine the effectiveness of using activated carbon and peat in reducing the selected VOCs emission from the petrol sample. The five selected VOCs analyzed in this research were benzene, toluene, p-xylene, m-xylene and oxylene. Generally, the study showed that the selected VOCs emitted from the petrol sample were greatly reduced when adsorbents were used. However, the analysis results indicated that activated carbons were superior in total selected VOC reductions than peat, inferring that the total surface area of the adsorbent materials affected the selected VOC adsorption capacity. The effect of the vessel size on the adsorption capacity using a fixed amount of adsorbent was also investigated. The study showed that activated carbon contained in long vessel had resulted in an increase of adsorbent column height and hence adsorbed more of the target VOCs. The overall results of the analysis concluded that activated carbon mixed with glass chips showed the hlghest percentage of VOC reduction as it adsorbed more selected VOCs due to its higher contact surface area. The averages in the reduction of benzene, toluene and xylene isomers were 80.81 %, 93.18% and 94.04 - 98.56% respectively